Pulmonary vein anatomy and its variations in a Turkish atrial fibrillation cohort undergoing cryoballoon-based catheter ablation - Duygu Kocyigit; Kadri Murat Gürses; Muhammed Ulvi Yalçın; Gamze Türk; Banu Evranos; Uğur Canpolat; Hikmet Yorgun; Tuncay Hazırolan; Kudret Aytemir (KARE Publishing, 2017)
Objective: Pulmonary vein (PV) anatomy has drawn attention since assumption that atrial fibrillation (AF) may originate from PVs and that electrical isolation of PVs may be beneficial in eliminating these triggers. The present study aims to investigate PV anatomy and its variations in a sample of Turkish patients undergoing PV isolation (PVI) for AF. Methods: 250 patients underwent multidetector computed tomography before cryoballoon-based PVI for AF. PV and left atrial (LA) anatomy were evaluated in 3-dimensional epicardial reconstructions. Results: 980 PVs were observed. All PVs drained into the LA. Mean superoinferior (SI) dimension for each vein was significantly larger than mean anteroposterior (AP) dimension. Accessory PVs were only seen on right side. Accessory veins were significantly smaller in both AP and SI diameter than other veins. Right-sided PV ostia were more round. Expected anatomy of 2 atrial ostia for right upper and lower lobe veins on each side was seen in 94.8% of patients. Remainder had other variant anatomy in right PVs. Conjoined ostium in the LA was seen in 35.6% of patients. Conclusion: PV variations were common in Turkish AF cohort undergoing PVI, which may be important to know about prior to ablation therapy for procedural success.